PENGARUH WAKTU PENGUKUSAN YANG BERBEDA TERHADAP KUALITAS PRESTO IKAN SEPAT SIAM (TRICHOGASTER PECTORALIS) - Hardianti Hardianti; Siti Aisyah; Findya Puspitasari (Fish Scientiae, 2019)
Presto is one the of the fish products processing by adding salt to the fish using high temperature and high pressure. The aim of this study was to know the effect of different steaming time on sepat siam (Trichogaster pectoralis) fish presto. The treatment used in this research is different steaming time (15, 30, 45 and 60 minutes) in the making of sepat siam fish presto. The result of this research showed that 45 minutes steaming time (treatment C) is the best treatment based on the organoleptic test in the specification ofthe texture and taste, but had no effect on the color and flavor specification and has no effect on chemical test for water content and protein (74.01% and 19.85%) respectively.